Comparison of Negative Pressure Wound Therapy and Conventional Therapy for Cranial Bone-exposed Wounds in Rabbits. Issue 4 (October 2017) - Chen, Lin; Li, Guorui; Liu, Sha; Ma, Xianjie; Li, Xueyong; Su, Yingjun; Guo, Shuzhong
Abstract : Background: Bone-exposed wounds with intact or defected periosteum are difficult to heal. To provide relevant experimental evidence for guidance of clinical therapy, we established a rabbit model to compare the efficacies of negative pressure wound therapy (NPWT) and conventional guaze dressing therapy on the healing of cranial bone-exposed wounds. Methods: Full-thickness excisional circular wounds of 2.0 cm in diameter with exposed bones covered with or without periosteum were created at the parietal regions in 88 rabbits that were further randomly divided into the following treatment groups: periosteum-intact wounds treated with conventional vaseline gauze dressings ( P + Control group), periosteum-intact wounds treated with NPWT (P + NPWT group), periosteum-lacking wounds treated with conventional vaseline gauze dressings (P-Control group), and periosteum-lacking wounds treated with NPWT (P-NPWT group). The wounds of NPWT groups were treated using a negative pressure therapy assembly that was set at a continuous pressure of −125 mm Hg for 7 days, then covered with vaseline gauze. The wound healing rates, wound infection rates, hydroxyproline content, and wound tissue histology were determined and evaluated. Results: The NPWT shortened the wound healing time by approximately 5 days when compared with the conventional gauze therapy. The histological characterization of wound tissues showed that NPWT decreased the inflammatory cells infiltration, accelerated reepithelialization and facilitated the organization of collagen fibers into neat layers on postoperative day (POD) 10. The NPWT enhanced bacterial clearances, reduced infection rates and increased the hydroxyproline contents in both types of wounds on PODs 10 and 15. The immunohistochemical staining of CD31 showed the NPWT treatment resulted in a significantly increased and persistent angiogenesis, and the wounds treated with NPWT showed well developed and more functional vessels at POD 7 compared with control. Conclusions: The NPWT is a more effective therapy for bone-exposed wounds than conventional guaze dressing therapy. The NPWT can promote bone-exposed wounds healing by increasing collagen contents and vessels densities while reducing inflammatory cells infiltration, reducing wound infection rates, and inducing an ordered collagen arrangement.